Volume 1: Pipeline and Facilities Integrity 2020
DOI: 10.1115/ipc2020-9511
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pressure Fluctuations on the Early Onset of Stage II Growth of High pH Stress Corrosion Crack

Abstract: Steel pipelines undergo the following sequential stages prior to high pH stress corrosion cracking (HpHSCC) failure, viz., formation of environmental condition, initiation of the intergranular cracks followed by cracks coalescence to form critical crack size (Stage I), mechanically dictated crack growth with higher rate (Stage II) compared to Stage I, rapid crack propagation to failure (Stage III). From fracture mechanics perspective, the crack size reaches the critical value at the onset of stage II; conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A horizontal loading machine was used to apply different loading waveforms to the pinhole-loaded precracked CT specimens. The authors' previous research 39 showed that the precracked CT specimen is at Stage 1b of HpHSCC crack growth when K max is equal to or below 15 MPa p m. Therefore, a K max of 15 MPa p m was selected for all of the loading scenarios in this study. In total, nine constant-amplitude loading waveforms were designed to study the effects of either amplitude or frequency of load fluctuation on Stage 1b of HpHSCC crack growth.…”
Section: Loading Parametersmentioning
confidence: 99%
See 4 more Smart Citations
“…A horizontal loading machine was used to apply different loading waveforms to the pinhole-loaded precracked CT specimens. The authors' previous research 39 showed that the precracked CT specimen is at Stage 1b of HpHSCC crack growth when K max is equal to or below 15 MPa p m. Therefore, a K max of 15 MPa p m was selected for all of the loading scenarios in this study. In total, nine constant-amplitude loading waveforms were designed to study the effects of either amplitude or frequency of load fluctuation on Stage 1b of HpHSCC crack growth.…”
Section: Loading Parametersmentioning
confidence: 99%
“…Thus, this condition can be considered as crack propagation in Stage 1b. 39 Figure 5 depicts the area near the precrack tip on the side faces of the CT specimens tested under three different R-ratios after polishing away the passive film and etching in Nital (5%). The frequency load cycles with an R-ratio of 0.9 were 5 × 10 −2 Hz, whereas the frequencies for R-ratios of 0.7 and 0.5 were 10 −2 Hz.…”
Section: The Magnitude Of Load Fluctuationsmentioning
confidence: 99%
See 3 more Smart Citations